Predicting survivors: animal temperament and translocation. (26th January 2016) - May, Tegan M.; Page, Manda J.; Fleming, Patricia A.
Lay Summary: Not all individuals are equally suited to translocation, and temperament traits have been shown to influence survival in a new environment. We developed and tested novel methods of temperament testing that fit within the translocation schedule for wild-caught animals, where handling has to be kept to a minimum, processing animals for other purposes reduces the amount of time available, and the degree of interference is limited due to ethics and welfare restrictions. Twitter: @western_web Abstract: Translocation is an important conservation management tool. However, not all individuals are equally suited to translocation, and temperament traits (e.g., boldness, reactivity, exploration, sociability, and aggression) are likely to influence survival in a new environment. A few empirical studies have examined the consequences of personality differences on captive-bred translocated animals, but this has not been done for wild-caught animals. We compared behavioral responses to trapping, processing, holding, and release for 56 wild common brushtail possums ( Trichosurus vulpecula ). Twenty individuals were captured twice, once to attach radio-tracking collars, the second time (2 weeks later) for the translocation. Consistency of behavioral responses was compared between capture events and radio-tracking allowed estimates of pretranslocation home range, rest site selection, and foraging behavior. Survivors ( n = 10 survivors, 5 months later) were individuals showing the most fear or emotional reactivity during holding (less likely to have slept, eaten, defecated, or nested) and those that had the smallest home ranges and selected the safest den sites in their original habitat. Conversely, the greatest increase in body mass was recorded for individuals that had demonstrated "unsafe" behavior in their original habitat. To our knowledge, this is the first time this type of behavioral screening during handling and holding prior to release as part of a translocation has been undertaken. These methods have broad applicability for screening potential translocation candidates and are easily translated to a range of threatened and vulnerable animal species.